Analisis dan Perancangan Sistem Informasi Showroom Mobil (SISMOB) Dengan Pendekatan Berorientasi Objek (Studi Kasus: UD. Tomaru Oto) - Muhammad Rheza Syafruddin; Ismiarta Aknuranda; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Tomaru Oto is dealer of car that has stood since the year 2000 was located in Mamajang, the city of Makassar, South Sulawesi. UD. Tomaru Oto sold the car in both the new and used. In running its business owners from UD. Tomaru Oto does all its business activities manually, both sales and purchase data recording, search sales and purchases data, and in calculating income and expense data. Based on these problems then needed an information system at the showroomcar (SISMOB). Building information system, needed requirements analysis and design of the system, in order for the system to be implemented in accordance with the needs of the user. The purpose of this study is to model the business processes, analyzing system design requirements and specifications, as well as to evaluate requirements and design specification system interface. This research use the BPMN to model business processes as well as the object-oriented approach to analysis and design of the system. Evaluation on research uses the preview on the use case, prototype and traceability matrix. The results of this research in the form of business process models of current and proposed specifications, features and system requirements, models of interaction, the model data and interface system as well as the results of the evaluation. Evaluation results showed that every requirement can be traced into the feature, the need and the model diagram. The results of the review showed that the flow of the user is in compliance with the flow on the use case specification.